Parâmetros genéticos e estudo de adaptabilidade, estabilidade em híbridos de maracujazeiro-amarelo - Cruz Neto, Alírio José da (2016)
The aims of this study were to evaluate the adaptability and stability of 14 yellow passion fruit plant hybrids and to estimate the genetic components of variance and average via mixed models (REML/BLUP), estimate the phenotypic, genotypic and environmental correlations between passion fruit characteristics in three environments. The selection of genotypes was based on methods of adaptability, as produced by the harmonic mean of genetic values (MHVG); of stability, as produced by the relative performance of genetic values (PRVG); and on a joint selection for both adaptability and stability, as produced by the harmonic mean of the relative performance of the genetic values (MHPRVG). The genetic correlations were estimated (rG), phenotypic (rF) and environment (rE) for each environment. The following traits were evaluated: fruit number (FN); total cumulative productivity (TCP); fruit mass (FM); fruit length (FL); fruit diameter (FD); peel mass (PM); peel thickness (PT); pulp mass (PUM); juice yield (JY); soluble solids (SS); titratable acidity (TA); and SS/TA (RATIO). The estimates for heritability and the genetic gains in the evaluated environments were found to have good perspectives for the selection of superior genotypes, except for traits TCP, SS, and JY. There was a marked effect from the genotype x environment interaction (GxE) for most traits, except for FL, JY, SS, TA, and SS/TA. The most stable and adaptable hybrids in the evaluated environments were BRS Gigante Amarelo (BRS Yellow Giant), HFOP-09, H09-09, GP09-02, GP09-03, and BRS Sol do Cerrado (BRS Sun of Cerrado). In 88.88% of cases the estimates of genotypic correlations were higher than phenotypic in the three environments. In Lençóis genotypic correlations between FN x FM, FD, PT, PM, PUM, SS and TA, differed from the other environments. In Dom Basilío and Rio de Contas to TCP correlated positively with FM, FL, FD and PM. In all environments the selection of fruits with higher FM facilitating higher LF, FD, PM and PUM and the selection of the oval thinner peel fruit shape. In general, for correlations between traits of agronomic importance, such as FN x TCP, SS; FM x FD, PM, PUM, RATIO; FD x FM, PUM, RATIO; FL/FD x PT e FM x RATIO showed the same behavior in the three evaluation environments, except for characteristics FN x FM, FD, PT, PM, PUM e TA in Lencóis.